Harvesting decellularized liver extracellular matrix from rodents for 3D scaffold fabrication - Meghana Kasturi; Kirthanashri S. Vasanthan (Artificial Cells, Nanomedicine, and Biotechnology)
Decellularization is a process to harvest the decellularized extra cellular matrix (dECM) that helps develop 3D scaffolds which mimic the native tissue composition. The decellularized tissues retain the structural and functional properties of the extracellular matrix (ECM) by an efficient decellularization process that retains tissue-specific biochemical and biophysical cues for tissue regeneration. In this study, we report an injection-based decellularization method, without perfusion setup. This study also compares the efficiency of the proposed protocol in the two animal models viz rat and mice. This method harvests rat and mice liver dECM using ethylenediamine tetra acetic acid (EDTA) and sodium dodecyl sulphate (SDS) within 08 h and 02 h respectively and preserved significant amount of ECM proteins. We reported that the harvested mice decellularized extracellular matrix (mdECM) and rat decellularized extracellular matrix (rdECM) had significant reduction in their DNA content (∼97%) and retained structural architecture resembling their native tissue counterparts. The total protein content retained in mdECM was ∼39% while that retained in rdECM was ∼65%. It was also found that the sGAG (sulphated glycosaminoglycan) content showed a no List of Figures.